FRI0113 Persistently High Disease Activity According to the ASDAS is Associated with Accelerated Radiographic Spinal Progression in Patients with Axial Spondyloarthritis. (10th June 2014) - Poddubnyy, D.; Haibel, H.; Braun, J.; Rudwaleit, M.; Sieper, J.
Abstract : Methods: Altogether 177 patients with definite axial SpA (100 with ankylosing spondylitis (AS) and 77 with non-radiographic axial SpA) from the German Spondyloarthritis Inception Cohort (GESPIC) were included in the current study. Spinal radiographs (cervical spine lateral views, lumbar spine lateral and anteroposterior views) were scored according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) system and for the presence of syndesmophytes. Clinical and lab data were collected at baseline and every 6 months thereafter. Time-averaged values of the CRP-based ASDAS, BASDAI and CRP over two years were calculated. Results: Rates of radiographic spinal progression were remarkably increased in patients with very high disease activity (time-averaged ASDAS>3.5) – table. There was a significant inter-group difference in rates of syndesmophyte formation between the groups of patients with ASDAS<1.3, 1.3≤ASDAS≤3.5, and ASDAS>3.5. Patients with very high disease activity had significantly higher odds for syndesmophyte formation as compared to patients with lower disease activity: odds ratio (OR)=5.5 (95%CI 1.89-16.04). In the logistic regression analysis, mSASSS progression by ≥2 points over two years was significantly associated with the time-averaged ASDAS: OR=1.58 (95%CI 1.02-2.44). Even stronger was the relationship between ASDAS and syndesmophyte formation/progression: OR=2.64 (95%CI 1.50-4.64). Interestingly, the association of ASDAS with syndesmophyte formation remained significant even after adjustment for time-averaged CRP: OR=2.16 (95%CI 1.13-4.11). When further known risk factors for radiographic spinal progression (syndesmophytes at baseline and smoking) were included in the model, the association of syndesmophyte formation with disease activity according to the ASDAS become slightly weaker: OR=1.91 (95%CI 0.99-3.69). In the univariate analysis, there was a significant association of syndesmophyte formation with the time-averaged CRP: OR=1.08 (95%CI 1.04-1.12), but no significant association with the BASDAI: OR=1.19 (95%CI 0.96-1.46). Similar associations were observed also for mSASSS worsening by ≥2 points over 2 years. Conclusions: Persisting very high disease activity according to the ASDAS is associated with radiographic spinal progression in axial SpA patients with disease duration <10 years. As demonstrated in the multivariate analysis, this effect is at least partially independent of the effect of CRP. We can hereby confirm such a recently described association found in AS patients with long-standing disease [2]. References: Poddubnyy D, et al. Arthritis Rheum 2012;64:1388-98. 2. Ramiro S, et al. Arthritis Rheum 2013;65(Suppl):S1215-6. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3578